Macroeconomic and Specific Banking Determinants of Nonperforming loans in Bosnia and Herzegovina - Agić, Zorana; Jeremić, Zoran (Industrija, 2018)
The aim of the research is to identify the macroeconomic and specific banking factors affecting the rate of nonperforming loans in the banking sector of Bosnia and Herzegovina (BiH). The authors assume that the three macroeconomic and five specific banking factors influence the quality of the loan portfolio. Aggregate data were used, which are taken from the Central Bank of BiH, Agency for Statistics of BiH and Labour and Employment Agency of BiH, and analyzed by descriptive statistics, correlation and regression analysis in the period from the first quarter of 2006 to the end of the fourth quarter of 2016. The empirical results show that there is a correlation between nonperforming loans and unemployment rate, inflation rates measured by the growth rate of consumer prices, return on assets and credit growth rates, while the impact of the growth rate of real gross domestic product, capital adequacy ratio, return on equity and active interest rates is not statistically significant.